PENGARUH FLUKTUASI NILAI TUKAR TERHADAP VOLUME EKSPOR KOMODITAS PERTANIAN TINJAUAN HUKUM EKONOMI DAN KEBIJAKAN PERDAGANGAN INTERNASIONAL - Aditya Putra Setyawan; Annie Myranika; Muhammad Fajar Alfahimi; Wisnu Cahyo Apriliyadi; Dwi Mani Suci Purwanto (CV. Lafadz Jaya, 2026)
This study analyses the impact of exchange rate fluctuations on the volume of agricultural commodity exports from the perspective of economic law and international trade policy. Employing a normative-empirical legal research method with a policy analysis approach, this study examines the dynamics of exchange rate regulation, its legal implications for agricultural exports, and the policy framework that supports trade stability. The results indicate that exchange rate fluctuations have a significant impact on the volume of agricultural commodity exports, both in the short and long term. A stable exchange rate policy is a crucial prerequisite for enhancing the competitiveness of agricultural products in international markets. This study recommends the harmonisation of monetary and trade policies to protect the interests of agricultural businesses and strengthen Indonesia’s position in global trade.